2021
DOI: 10.1063/5.0049165
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on formation mechanism of main droplets and elimination method of satellite droplets in jet process

Abstract: In certain industries, such as the Chinese pharmaceutical pill preparation medicines, the occurrence of satellite droplets and the inconsistent diameters of the main droplets lead to wasted resources and affect the normal operation of the production system. So it is necessary to investigate the formation process of main droplets and the elimination method of satellite droplets in the jet process. In this paper, the effects of the liquid level height, dropper inner diameter, and glycerin mass fraction on the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Runze et al performed experiments with a 50 % glycerol-water solution and observed that applying longitudinal disturbances at a frequency of 84Hz induced asymmetry in the droplet's shape, resulting in oscillations and distortion. However, during the entire process, only one breakage occurred, and no satellite droplets were generated [ 56 ]. Oke Oktavianty et al conducted a comparison between the basic waveform, W-shaped pulses, and enhanced W-shaped pulse waveforms.…”
Section: Inkjet Printing Quality Optimizationmentioning
confidence: 99%
“…Runze et al performed experiments with a 50 % glycerol-water solution and observed that applying longitudinal disturbances at a frequency of 84Hz induced asymmetry in the droplet's shape, resulting in oscillations and distortion. However, during the entire process, only one breakage occurred, and no satellite droplets were generated [ 56 ]. Oke Oktavianty et al conducted a comparison between the basic waveform, W-shaped pulses, and enhanced W-shaped pulse waveforms.…”
Section: Inkjet Printing Quality Optimizationmentioning
confidence: 99%